Analysis of light trapping effects in Si solar cells with a textured surface by ray tracing simulation - Byun, Seok-Joo; Byun, Seok Yong; Lee, Jangkyo; Kim, Jae Wan; Lee, Taek Sung; Cho, Kyuman; Sheen, Dongwoo; Tark, Sung Ju; Kim, Donghwan; Kim, Won Mok (ELSEVIER SCIENCE BV, 2011)
The effects of the size and density of a pyramidal texture, as formed on the surface of Si solar cells to increase the light trapping efficiency, on the optical reflectance and absorptance were examined by comparing simulation results and experimental observations. A ray tracing algorithm capable of the direct calculation of the absorbed energy in active Si was utilized for the simulation. The simulation results showed that the optical reflectance spectra, i.e., the absorptances, of the textured surface with a fixed density of pyramids were not affected by the pyramid pitch, whereas the spectra with varying density of pyramids decreased with an increase in the density of the pyramids. Observations similar to the simulation results were observed from the experimentally textured surfaces, indicating that the density of the pyramid area, i.e., the area of the flat region, is the most crucial factor affecting the optical behavior of a textured Si surface with three-dimensional pyramid patterns. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CONCENTRATOR